Clinical and biomechanical perspectives on runner’s knee: a literature-based review of patellofemoral pain syndrome - Kadłubowska, Karolina; Sikorski, Adam; Szaryński, Mikołaj; Jakubowska, Paulina; Chojnowska, Natalia; Rytel, Jan; Jakubowska, Martyna; Bursztyn, Michał; Bursztyn, Tomasz; Gólcz, Adrian; Gólcz, Julia (Quality in Sport, 2025)
Patellofemoral Pain Syndrome (PFPS), widely known as runner’s knee, is one of the most common yet frequently misunderstood causes of anterior knee pain in active individuals. This review highlights the multifactorial nature of PFPS, emphasizing the complex interplay between biomechanical dysfunction, muscular imbalances, anatomical variations, overuse, and psychological influences. The article synthesizes current evidence on pathophysiology, clinical presentation, risk factors, and diagnostic challenges, demonstrating why accurate identification of PFPS remains difficult and often requires a comprehensive, cluster-based clinical approach. Special attention is given to the role of hip and quadriceps weakness, abnormal lower-limb alignment, and altered movement patterns in generating patellofemoral overload. The review also evaluates contemporary treatment strategies, with strong support for conservative, exercise-based rehabilitation focused on strengthening, movement retraining, flexibility, and patient education. Adjunctive tools such as taping, bracing, and orthoses are discussed as supportive options rather than primary interventions. Early, individualized therapy is essential for preventing chronic symptoms and enabling a safe, lasting return to physical activity.